the Role of Marketing Intelligence and Marketing Architecture Based Technology Assist in the Development of Business on the Msmes Maount Bromo Probolinggo in East Java (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2017)
This research aims to provide a paradigm change business players in order to develop business in the manage with the help of a smart marketing and design technology sophisticated pengolaan governance and business can be developed with good, and can increase community economic welfare levels in the vicinity of micro and small and medium enterprises Mount Bromo Probolinggo East Java, empirically the economy in and around micro and small and medium enterprises probolinggo is still not optimal and the support of the government also has not been maximum attempts to help businesses on micro and small and medium enterprises around Gunung Bromo Probolinggo. Researchers attempting to help to resolve the problems of the economy in and around Mount Bromo by trying to examine the variables related to the smartphone technology-based marketing and technology based marketing design also in order to help the micro and small and medium enterprises can solve problems usahannya that there are still many obstacles. Researchers took samples around 100 people merchants who have micro and small and medium enterprises Business around Mount Bromo and using the methods of quantitative analysis and using the appliance AMOUS SAM analysis and location already determined around Mount Bromo, from a ) is expected to found a positive result against the business development of micro and small and medium enterprises and can help the sales profit level and can improve the level of technology used by entrepreneurs and increase the level of community welfare micro and small and medium enterprises Mount Bromo Probolinggo in East Java.